2020
DOI: 10.3390/ma13112476
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Methods for Assessing the Influence of Improper Asphalt Mix Compaction on Its Performance

Abstract: Compaction index is one of the most important technological parameters during asphalt pavement construction which may be negatively affected by wrong asphalt paving machine set, weather conditions, or the mix temperature. Presented laboratory study analyzes the asphalt mix properties in case of inappropriate compaction. The reference mix was designed for AC 11 S wearing layer (asphalt concrete for wearing layer with maximum grading of 11 mm). Asphalt mix samples used in the tests were prepared using Marshall d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…The results showed that the effects of the VVTM and SGC method were basically equivalent, and they were both better than the Marshall method. This is also consistent with the relevant research conclusions of the research group [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that the effects of the VVTM and SGC method were basically equivalent, and they were both better than the Marshall method. This is also consistent with the relevant research conclusions of the research group [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 92%
“…In the past 20 years, China’s traffic has been developing towards “large flow, heavy axle load, high tire pressure”, and some disadvantages of the Marshall method have become obvious [ 10 , 11 , 12 ]. The SMA pavements designed by the Marshall method with early ruts, oil spills, and water seepage indicate that the Marshall compaction standard cannot meet current traffic requirements [ 9 , 13 , 14 , 15 ]. In addition, the Marshall specimen has a poor correlation with the mechanical properties of the site so that the test indicators of the specimen produced by the Marshall method in the laboratory cannot determine the quality of the field pavement very well [ 9 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier based on Figure 2 , the SEM image of the GRP-WP reveals that GRP-WP contains a considerable amount of micro-sized chopped glass fibers (CGF). Due to the irregular shapes of these CGFs, they have significantly longer lengths compared to their widths, and they might have negatively impacted the workability of the asphalt mixtures, causing a reduction in compaction, as discussed by several other studies, such as those presented by Melotti et al [ 56 ] and Wróbel et al [ 57 ]. Resistance to compaction might be one of the main reasons why Va results increase as GRP-WP content increases.…”
Section: Discussionmentioning
confidence: 99%
“…The compaction index is one of the most important technological parameters during asphalt pavement construction, which may be negatively affected by the wrong asphalt paving machine setting, weather conditions, or the mix temperature. Presented in [ 27 ], this laboratory study analyzes the asphalt mix properties in case of inappropriate compaction. The reference mix was designed for an AC 11 S wearing layer (asphalt concrete for a wearing layer with maximum grading of 11 mm).…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%